LUNG FUNCTION AND RESPIRATORY MUSCLE STRENGTH IN OBESE IN CHILDREN - E. G. Furman; A. M. Yarulina; L. V. Sofronova (Union of pediatricians of Russia, 2015)
Background. It is known that obesity may influence the state of respiratory function and it is associated with a number of diseases of the respiratory system. Obesity in itself, even in the absence of other known causes, can cause a feeling of shortness of breath at rest. At the same time, the cardinal symptom of respiratory muscle weakness is shortness of breath, which promotes the reduction of exercise tolerance. At the moment the problem state of respiratory function and respiratory muscles in children with different degrees of obesity is relevant and understudied. Aim. Investigation of lung function and respiratory muscle strength in obese in children. Methods. 46 children with obesity were examined, with a prevalence of obesity of mixed origin with progressive, aged 7 to 16 years. We evaluated the lung function and strength of respiratory muscles in the form of maximum inspiratory pressure at the mouth (MIP), maximal expiratory pressure at the mouth (MEP) and nasal inspiratory pressure in the sniff-test (SNIP). Results. The children with obesity complained of dyspnea. The respiratory muscle dysfunction observed in the form of reduction of its forces. Reduced respiratory muscle strength ( 80% of the norm) was in 44% of patients on the MIP and 38% on the MEP and was increased with increasing body mass index. Conclusion. Children with obesity need to monitor the lung function and evaluate the strength of the respiratory muscles for early detection of functional disorders of the respiratory system.